Perkembangan Diri Pemuda Autis Yang Tidak Bersekolah - Aldjon Nixon Dapa (Jurnal Ilmiah Wahana Pendidikan, 2020)
Autism is one of the disorders carried out by Children with Special Needs or ABK. Autism disorder is a disorder that causes children to have behaviors that do not care about their social environment so that it can affect the development of interaction as well as communication. To practice social interaction, special assistance and knowledge from parents and families are needed. Parents as the first social environment known as children who have a very important role to improve the ability of children in all respects. Specifically, the purpose of this study is to look at how parents are handling autistic children as seen from parents' attention, parental knowledge and assignments from parents to children. Also see the development of children with the development of intelligence, social interaction and physical abilities of children. This research uses a phenomenological qualitative research method by looking at and managing parents and also the development of autistic children in early adulthood. The subject in this study was one adult with autism who was not in school. In this study, researchers used data collection techniques through observation and interviews. Observations made were participant observation and researchers interviewed the subject's mother as a respondent. The results showed that parents' handling of children was quite good in terms of attention and assignment of tasks for child development in logistical aspects, social interaction as well as children's physical abilities. But in terms of parental knowledge is still lacking.